Stakeholder perspectives regarding alternate approaches to informed consent for comparative effectiveness research. Issue 2 (5th December 2017) - Morain, Stephanie R.; Tambor, Ellen; Moloney, Rachael; Kass, Nancy E.; Tunis, Sean; Hallez, Kristina; Faden, Ruth R.
Abstract: Introduction: Traditional informed consent approaches, involving separate discussions and lengthy consent forms, may be an imperfect fit for comparative effectiveness research (CER) that is integrated into usual care and compares non‐investigational treatments. However, systematic efforts to collect broad stakeholder perspectives about alternative streamlined approaches to disclosure and consent in this context have been limited. Methods: We used a deliberative engagement method to solicit the views of a multi‐stakeholder group regarding 3 alternative models of disclosure, consent, and authorization in CER studies: Opt‐In, Opt‐Out, and "General Approval". Participants considered the acceptability of these 3 models for observational and randomized CER studies of hypertension medications and for alternative treatments for spinal stenosis, all conducted in the context of a learning health care system. Results: Fifty‐eight stakeholders participated in the all‐day deliberative engagement session. Following deliberation, a majority of stakeholders (67%) liked the General Approval model for the observational hypertension study, more than the number who reported liking Opt‐Out or Opt‐In (45% and 36%, respectively). Support was lower for General Approval model in the context of a randomized hypertension study, with 80% liking a traditional Opt‐In approach, compared with 54% liking Opt‐Out, and 11% liking General Approval. Similarly, for the spinal stenosis CER studies, while most stakeholders preferred a streamlined Opt‐Out approach for the observational design, most preferred a traditional Opt‐In approach for the randomized version. Conclusions: This multi‐stakeholder group was more favorable towards streamlined models for disclosure and authorization for observational CER than randomized designs. These findings are consistent with arguments that informed consent requirements should be tailored to the context of the research design, rather than a standard "one size fits all" approach.